Isoprene chain shuttling polymerisation between cis and trans regulating catalysts: straightforward access to a new material. Issue 38 (27th April 2017) - Phuphuak, Y.; Bonnet, F.; Stoclet, G.; Bria, M.; Zinck, P.
Abstract : Isoprene chain shuttling polymerisation between the 1, 4- trans regulating Cp*La(BH4 )2 (THF)2 /Mg n BuEt (Cp* = C5 Me5 ) and the 1, 4- cis regulating NdCl3 (THF)2 /AlR3 (R = Et or i Bu) systems provides access to stereoblock polyisoprene. Abstract : Isoprene chain shuttling polymerisation between the 1, 4- trans regulating Cp*La(BH4 )2 (THF)2 /Mg n BuEt (Cp* = C5 Me5 ) and the 1, 4- cis regulating NdCl3 (THF)2 /AlR3 (R = Et or i Bu) systems provides access to stereoblock polyisoprene. Under selected experimental conditions, the trans segments are semi-crystalline, leading to a thermoplastic elastomer-like material.